LECTURERS' PERFORMANCE IN PANDEMI PERIOD: VIEWED FROM READINESS FOR CHANGE AND LECTURERS' COMPETENCE - Nita Kanya (INFOKUM, 2023)
The existence of the COVID-19 pandemic has had a huge impact on human life, one of which is in teaching and learning activities. Both students, teachers and agencies are required to adapt to the situation and change learning methods to distance learning (online). The purpose of this research is to look for the factors that affect lecturer performance, especially in terms of competence and readiness for change in lecturers. This study uses a quantitative approach to statistical analysis used is the multiple regression method assisted by the JASP application. The measuring instruments used are arranged using a Likert scale based on various theories. From the results of this study, it is hoped that it can be developed in the form of intervention or training to increase teacher readiness in dealing with change, which is based on leadership and organizational culture variables. Based on the results of the study, it was found that competency and readiness for change in lecturers have a significant influence on lecturer performance both partially and simultaneously.